In-vitro Antioxidant activity assay of Habenaria longicorniculata J. Graham wild medicinal tubers - Satish, BN; Mallya, Suma V (Journal of Drug Delivery and Therapeutics, 2019)
About: Habenaria longicorniculataJ.Graham are wild medicinal orchids with immunomodulatory and rejuvenating properties. Hence it has been tested to evaluate its antioxidant property. Materials and methods: Tubers were collected from Western-ghats during flowering season, shade dried, powder prepared and used for further study. In vitro antioxidant activity for DPPH, Nitric oxide, Hydroxyl radicals and inhibitory activity for Hydrogen peroxide was planned as per standard protocol. Results: The antioxidant activity property of H. longicorniculata J. Graham tuber extract exhibited the IC50 value for DPPH >1000, for NO and OH >5000 and inhibitory activity for H2O2 68.6189 respectively. Thus tubers of test drug proved to be potent H2O2 inhibitor. Keywords: Habenaria longicorniculataJ.Graham, In vitro antioxidant, H2O2